AUDIT DAN TATA KELOLA SISTEM INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 PADA KSP SRI SATYAM SEDANA - Sang Putu Bayu Krisnanda Wiguna; I Gusti Agung Pramesti Dwi Putri; Ni Made Estiyanti (Politeknik Bisnis Indonesia, 2024)
In this study, the author aims to assess the accounting information system that has been used by the Sri Satyam Sedana cooperative and to make an assessment of the company‘s performance during the period of using the system. The research method used is the experiment/ method, which is to test the hypothesis about the cause and effect of a thing. This type of research method requires a comparison or comparison between before and after experimental research. COBIT is a complete and comprehensive standard as an IT audit framework because it is continuous/y developed by ISACA, a professional auditor institution spread across almost all countries. IT governance is something that every company needs to pay attention to. This is because IT Governance can be used by organizations at the executive level where it is to control risks that can occur and ensure that all forms of company resources can be used appropriately. With good corporate governance, it can affect the level of trust and investment protection in the future that is more secure.